2012
DOI: 10.1007/s11242-011-9937-0
|View full text |Cite
|
Sign up to set email alerts
|

A Mathematical Model and Analytical Solution for the Fixation of Bacteria in Biogrout

Abstract: Biogrout is a new method for soil reinforcement, which is based on microbialinduced carbonate precipitation. Bacteria and reactants are flushed through the soil, resulting in calcium carbonate precipitation and consequent soil reinforcement. Bacteria are crucially important in the Biogrout process since they catalyse the reaction. Hence, to control the process, it is essential to know where the bacteria are located. The bacteria are possibly in suspension but can also be adsorbed or fixated on the matrix of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…In van Wijngaarden (2013), it has been shown that small deviations in the flow equations have a minor effect on the final calcium carbonate content.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In van Wijngaarden (2013), it has been shown that small deviations in the flow equations have a minor effect on the final calcium carbonate content.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“… The downward infiltration of cementation solution has little dispersion and diffusion through the column (Van Wijngaarden et al 2012).…”
Section: Assumptions Of Mathematical Modelmentioning
confidence: 99%
“…These models describe bacterial growth and predict the changes in the characteristics of the porous media like the permeability and porosity [22]. Among bacterial growth models in porous media, there are the Darcy continuum models [24,29], bacterially based models [16], Lattice Boltzmann-based simulations [9,17], and pore network models (PNM) [6,8,18,21,23,26,28]. The secretion of extracellular polymeric substances (EPS) by bacterial population causes the formation and growth of biofilm on the walls of the porous media.…”
Section: Introductionmentioning
confidence: 99%